EFEKTIVITAS MODEL CLOSED LOOP DALAM AGRIBISNIS CABAI RAWIT: TINJAUAN SOSIAL, EKONOMI, DAN LINGKUNGAN - Sukmawati, Dety; Dasipah, Euis; Nurlaela, Irma; Mahmiludin, Dede; Marina, Ida (Journal of Sustainable Agribusiness, 2025)
This study analyzes the effectiveness of the Closed Loop model in chili pepper agribusiness in Sukabumi Regency through social, economic, and environmental perspectives. The research employed a quantitative survey method involving 32 partnered farmers who have participated in the Closed Loop program since 2021. Data were collected through questionnaires, interviews, observations, and secondary sources, and analyzed using descriptive statistics and multiple linear regression. The results show that the implementation of the Closed Loop model has expanded from 1.3 hectares with 20 farmers in 2021 to 25 hectares with 32 farmers in 2023. Social factors, particularly farmer participation, institutional performance, and stakeholder trust, were found to have the strongest influence on the program’s effectiveness. Economically, partnered farmers experienced higher price stability and better access to financing and inputs compared to non-partnered farmers, although production costs and uneven adoption of technology contributed to varied income levels. Environmentally, the adoption of eco-friendly practices remained limited, with most farmers still using chemical-based inputs, contributing to productivity fluctuations and environmental pressure. These findings indicate that the effectiveness of the Closed Loop model depends on the strengthening of social capital, institutional capacity, and environmentally sustainable practices. To enhance the model’s performance, intensive farmer coaching, improved cooperative management, and environmentally sustainable cultivation strategies are recommended